(untitled) (Journal of the College of Basic Education, 2022)
The art of designing fabrics is one of the most important arts that are related to industry and associated with science, as it is an art based on the textile industry. Bedding fabric designs have witnessed a clear deterioration as a result of excessive importation of this type of product. Therefore, the current research was summarized in three chapters. The first dealt with the research problem, which is summarized as follows: The adoption of harmony and contrast in the design of Iraqi furniture fabrics? As for the aim of the research, it is to identify harmony and contrast in the designs of upholstery fabrics, and for the second chapter, it included three axes. The first dealt with harmony and contrast in the designs of fabrics.